Development of Autograph-Assisted Teaching Materials to Enhance Students’ Numeracy Skills in Phase D - Loska, Febri; Zetriuslita, Zetriuslita; Effendi, Leo Adhar; Amelia, Sindi; Hidayat, Riyan (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2025)
The numeracy skills of Phase D students in Indonesia remain relatively low, as evidenced by the 2018 PISA survey, which ranked Indonesia 72nd out of 79 countries. Transformational geometry is one of the topics that demands high numeracy, often posing challenges due to the need for spatial visualization and logical reasoning. While previous studies have shown the potential of Autograph in HOTS-based learning, research on the development of Autograph-assisted teaching materials explicitly designed to enhance numeracy remains limited. This study introduces a novel approach by integrating Autograph into numeracy-oriented materials for transformational geometry, aiming to provide a validated and practical resource for classroom use. The research employed an R&D design with the ADDIE model, involving 36 ninth-grade students and a mathematics teacher at UPT SMP Negeri 4 Siak Hulu. Data were collected using validation sheets, response questionnaires, and pretest–posttest numeracy tests, and analyzed through Aiken’s V, practicality percentage, N-gain, paired t-test, and Cohen’s d. The results indicated high validity (0.88), high practicality (84.6%), and strong effectiveness (N-gain = 0.78, Cohen’s d = 2.7), with significant improvement from pretest to posttest. The findings highlight the novelty of employing Autograph to foster numeracy development in middle school mathematics, offering new insights into technology-supported instructional design. However, the absence of a control group suggests the need for further studies using more rigorous experimental designs.